Learner attitudes toward error correction in a beginners English class - Abarca Amador, Yohanna (Instituto Tecnológico de Costa Rica, 2013)
This study was conducted among twenty-three college students of English who were asked their preferences for twenty error correction techniques. The techniques were presented mostly in dialogue form as they actually take place in the classroom. The study shows that the students preferred those techniques in which they are explicitly told what their mistake was. In light of this, the students favored correction by their teacher, not their peers in the language class. The students also showed their preference for the techniques in which they are given the opportunity to repeat the correct model provided by the teacher and thus repair their faulty speech. The study concludes that these techniques provide a type of corrective feedback that encourages students to participate in the correction of their spoken errors, a classroom activity that leads to acquisition of the foreign language.